Estudo da sinterização do compósito WC-316L - Santos, Alessandra Agna Araújo dos (2013)
The hard metal is a metal matrix composite composed hard phase carbide and a ductile phase, which can be cobalt, nickel or iron, which plays the role of a hard phase and binder gives the material an adequate toughness. The main binder used in composite based on WC is cobalt. Cobalt however is a scarce material having high processing costs and is toxic. This study analyzed the influence of 316L stainless steel sinter WC, analyzing the possibility of replace cobalt by 316L stainless steel. The 316L stainless steel has similar physical characteristics to cobalt and is more economical and non-toxic processing. The composite WC-316L was processed by powder metallurgy following steps: preparing starting powders, milling (grinding balls ratio 7:1) to damp presence of cyclohexane for 5 hours, compaction of 200 MPa, sintering at different temperatures: 1200oC , 1300oC and 1400oC with rate 20oC/min isotherm 60 minutes in vacuum atmosphere. The starting powders WC and 316L were characterized by X-RD diffraction, particle size testing and scanning electron microscopy (SEM). The composite sintered WC- 316L was characterized by SEM and micro vickers hardness test. The samples processed at temperatures of 1200oC and 1300oC showed high porosity heterogeneity microstructural, low relative density, 58 % and 66 % respectively, and low hardness, 300 HV and 700 HV, respectively. The samples sintered at temperature 1400oC showed higher homogeneity microstructural compared to the samples sintered at temperatures of 1200oC and 1300oC , relative density of 86 %, and micro hardness value of 1890 HV.